Odnowienia sosny zwyczajnej Pinus sylvestris L. w Karpatach w zależności od żyzności siedliska - Ambroży, Sławomir; Kapsa, Mariusz (Leśne Prace Badawcze, 2019)
The aim of this work was to determine the biometric features of Scots pine Pinus sylvestris L. regeneration in terms of their susceptibility to weather-inflicted damage. We compared the damage between three sites located in the Polish part of the Carpathians: Scots pine planted in (I) fertile sites of mountain broadleaved and mixed broadleaved forest, (II) poor sites of mountain coniferous forest and (III) sites of Scots pine natural refuges during the post-glacial period. In each of the three sites of pine regeneration, 11 research plots were established with 50 pine trees on each plot. For each tree, the following biometric measurements were taken: diameter at breast height, height, three-year height increment, crown length and crown width measured along the contour line. The Scots pine regeneration was found to vary in terms of their biometric features depending on the site fertility. In fertile sites, the biometric parameters of the trees increased at a faster rate compared to low-fertility sites causing an increase in their susceptibility to damage by adverse weather conditions such as snow and rime. Therefore, the silvicultural risk in fertile sites is high and thus the introduction of pine for regeneration should be avoided in fertile broadleaved and mixed broadleaved forests even if pine provenances from a mountain origin are to be planted. Furthermore, tending cuts in regeneration should be made frequently, but with moderate intensity as to avoid excessive reductions in tree density. Intensive cuts, especially in fertile sites, promote the expansion of pine crowns, which further increases the risk of damage.